تكوين النادي العربي لتنمية مهارة القراءة بالمدرسة الثانوية الإسلامية الحكومية غنوءواتو بجومبانج - إقناع السلام (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2015)
The basic ending of teaching reading skills is how the students are able to read Arabic language from right to left easily and gratify. The fact that reading skills are still difficult and tedious for students. Researcher found that the problem or difficulty stems from ineffective and pull learning strategy used by a teacher.Based on the above problems, researcher submit questions formulation of the problem as follows: (1) How do I create Learning Strategy of An-Nadi Al-Arabi to increase reading skills at Government Islamic Senior High School of Genukwatu Jombang?, (2) How far the effectiveness of Learning Strategy of An-Nadi Al-Arabi to increase reading skills especially for reading fluently at Government Islamic Senior High School of Genukwatu Jombang?, (3) How far the effectiveness of Learning Strategy of An-Nadi Al-Arabi to increase reading skills especially for reading comprehension at Government Islamic Senior High School of Genukwatu Jombang?.The purposes of this study are: (1) Knowing positive effect of creating Learning Strategy of An-Nadi Al-Arabi to increase reading skills at Government Islamic Senior High School of Genukwatu Jombang, (2) Knowing the extent of the effectiveness of Learning Strategy of An-Nadi Al-Arabi to increase reading skills especially for reading fluently at Government Islamic Senior High School of Genukwatu Jombang, (3 Learning Strategy of An-Nadi Al-Arabi to increase reading skills especially for reading comprehension at Government Islamic Senior High School of Genukwatu Jombang.This research method is research and development (R & D). The research population is all students of tenth Class of Government Islamic Senior High School of Genukwatu Jombang, amounting to 109 students in school year 2010-2011. And researcher toke the research sample amounting to 30 % from all population, namely amounting to 13 students.The results of this research can be concluded that: (1) Design of Learning Strategy of An-Nadi Al-Arabi to increase reading skill consists of : understanding of the product, elements of the product, basis of the product, purposes of reading skill, purposes of teaching by using the product, matters of the product, application of the product, making steps of learning strategy, arrangement of places or positions, and assessment, (2) The number of average value of pre-test in the teaching of reading skill is 73,106, and The number of average value of post-test in the teaching of reading skill is 82,273, (3) The application of learning Strategy of An-Nadi Al-Arabi to increase reading skill is effective because the value of t : 14,10446.